Protecting the Distribution of Color Images via Inverse Colorization, Visible-Imperceptible Watermarking and Reversible Data Hiding - Eduardo Fragoso-Navarro; Francisco Garcia-Ugalde; Manuel Cedillo-Hernandez (IEEE Access, 2023)
Invertible color-to-gray algorithms are good alternatives for protecting color images in storage, transmission, or limited-access environments. These approaches hide color information in a gray-scale version of an image. Thus, illegal recovery of the original color becomes a challenging task, and only authorized users can restore the colorized image. However, although the color is protected, the original structure of the image remains vulnerable to illegal usage. In this paper, we present a reversible distortion of the protected gray-scale image to make illegal reconstruction more difficult. In addition, we preserve the general visibility of the original content. Furthermore, a visible imperceptible watermark is embedded to protect ownership of the colorized image in public access. The watermark remains imperceptible in the colorized image and reveals the logo of the owner when the image is protected. We propose different levels of distortions obtaining mean PSNR qualities between 14.74 dB and 32.92 dB with respect to a reference gray-scale image. Furthermore, the mean PSNR quality of the colorized images remains between 38.87 dB and 41.55 dB.